2011
DOI: 10.1021/ol103107v
|View full text |Cite
|
Sign up to set email alerts
|

Mild and Selective Vanadium-Catalyzed Oxidation of Benzylic, Allylic, and Propargylic Alcohols Using Air

Abstract: Transition metal-catalyzed aerobic alcohol oxidation is an attractive method for the synthesis of carbonyl compounds, but most catalytic systems feature precious metals and require pure oxygen. The vanadium complex (HQ)(2)V(V)(O)(O(i)Pr) (2 mol %, HQ = 8-quinolinate) and NEt(3) (10 mol %) catalyze the oxidation of benzylic, allylic, and propargylic alcohols with air. The catalyst can be easily prepared under air using commercially available reagents and is effective for a wide range of primary and secondary al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(87 citation statements)
references
References 50 publications
1
86
0
Order By: Relevance
“…As shown in Figure 6, saturation magnetizations for Fe 3 Based on the previous studies, 20 a possible mechanism for the aerobic oxidation of alcohols in the system was proposed as shown in Scheme 2. The formation of aldehydes might be occurred through a SN1 mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 6, saturation magnetizations for Fe 3 Based on the previous studies, 20 a possible mechanism for the aerobic oxidation of alcohols in the system was proposed as shown in Scheme 2. The formation of aldehydes might be occurred through a SN1 mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Many efforts have been devoted to the field with a variety of catalysts been developed such as metal complexes, [3][4][5][6] tetramethylpiperidinyloxide (TEMPO), [7][8][9] heteropoly acids 10,11 and so on. Nevertheless, organic solvents are usually used to promote the reaction process, which is considered to be contrary to the concept of green chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the well-investigated nitrogen-based ligands, few organometallic complexes with phosphines have been applied in the oxidation of alcohols [6][7][8][9][10][11][12][13]. For example, palladium-catalyzed oxidations with tertiary phosphine oxide (TPO), which have been extensively used in cross coupling reactions, are quite limited [14,15].…”
Section: Organometallic Catalystsmentioning
confidence: 99%
“…Blay et al reported cobalt(III) complex catalyzed aerobic oxidation of propargylic alcohols (r.t., 60%-97% yield). [17] Recently Hanson and co-workers reported another vanadium-catalyzed oxidation of benzylic, allylic and also propargylic alcohols using air (60-100 ℃, 38%-98% yield), [18] the catalyst was easily prepared and efficient for a wide range of α,β-unsaturated alcohols. Recently we also reported a mild and practical Fe(NO 3 ) 3 /TEMPO-catalyzed aerobic oxidation of benzylic, allylic, propargylic alcohols, and normal alkanols, allenols expedited by a catalytic amount of sodium chloride.…”
Section: Introductionmentioning
confidence: 99%